Elevated alpha-fetoprotein in a 3-month-old infant: the significance in a patient with beckwith-wiedemann syndrome - Wong, Suet Yin; Samsudin, Intan Nureslyna; Abdul Hamid, Hanisah; C. Thambiah, Subashini; Lai, Yin Ye; Zahari Sham, Siti Yazmin (Universiti Putra Malaysia, 2023)
A 3-month-old female infant with omphalocele, posterior cleft palate and bilateral hydronephrosis was inadvertently discovered to have macroglossia, hepatomegaly, and facial nevus flammeus during hospitalisation for community-acquired pneumonia. A clinical diagnosis of Beckwith-Wiedemann syndrome (BWS), a disease with a higher predisposition to developing embryonal tumours was made. A liver ultrasound revealed a haemangioma at section VIII with the absence of hepatoblastoma. A serum alpha-fetoprotein (AFP) of 413 IU/mL was initially a concern given it was 60 times higher than the stated reference interval but was noted to be age-appropriate and related to the patient’s underlying disease. This case report highlights the importance of reporting an AFP age-specific reference interval as well as the necessity of monitoring AFP in a child with BWS due to the higher risk of hepatoblastoma.